2022
DOI: 10.1007/s12519-021-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking status during pregnancy and low birth weight in offspring: systematic review and meta-analysis of 55 cohort studies published from 1986 to 2020

Abstract: Ethical approval Not needed. Conflicts of InterestWe declare that we have no conflicts of interest. Data availability statementStudies used for meta-analysis are listed in Supplementary eTable 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 74 publications
1
12
1
Order By: Relevance
“… 37 , 38 There have also been some reports that caffeine is associated with an increased risk of FGR 10 , 11 and several meta-analyses have demonstrated an increased risk of lower birthweights. 3 , 4 In our study, we did not observe any such risk after multivariable adjustment that included an objective measure of smoking. We hypothesized that this is because there is a strong correlation between paraxanthine and smoking, that has been recognized elsewhere 26 and that was more fully controlled for in our regression models by using an objective measure to assess smoking.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“… 37 , 38 There have also been some reports that caffeine is associated with an increased risk of FGR 10 , 11 and several meta-analyses have demonstrated an increased risk of lower birthweights. 3 , 4 In our study, we did not observe any such risk after multivariable adjustment that included an objective measure of smoking. We hypothesized that this is because there is a strong correlation between paraxanthine and smoking, that has been recognized elsewhere 26 and that was more fully controlled for in our regression models by using an objective measure to assess smoking.…”
Section: Discussioncontrasting
confidence: 56%
“…These recommendations come from decades of research that have assessed their relationship with pregnancy complications. For instance, smoking during pregnancy is associated with an increased risk of fetal growth restriction (FGR), 1 spontaneous pre-term birth 2 and low birthweight 3 , 4 but a reduced risk of pre-eclampsia (PE). 5 The paradoxical effect on PE risk is thought to be related to the effects of smoking on pro-angiogenic proteins, such as increasing placental growth factor (PlGF), and anti-angiogenic proteins, such as decreasing soluble fms-like tyrosine kinase 1 (sFlt-1), 6 though data are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…We also found evidence of an association between higher I:Cr and higher birth weight, up to a threshold of around 200 μg/g, but not for UIC. The potential size of the associations identified was relatively modest compared to other established modifiable risk factors for lower birth weight and SGA, such as smoking [ 46 , 47 , 48 ], alcohol [ 49 , 50 ] and caffeine [ 51 , 52 , 53 ], and small enough to be potentially explained by bias in study design, analysis, or selective publication. There was no evidence of an association with preterm delivery, though only two studies reported results for spontaneous preterm delivery.…”
Section: Discussionmentioning
confidence: 95%
“…We relied on a review of the literature and a directed acyclic graph (DAG) to identify possible confounders, including maternal age [ 27 ], family monthly income per capita (< 2500 RMB; 2500–4000 RMB; >4000 RMB) [ 28 ], parental education level (junior high school or below; senior middle school; junior college; bachelor’s degree or above) [ 29 ], maternal pre-pregnancy BMI [ 30 ], paternal BMI [ 31 ], parity (multipara; nulliparous) [ 32 ], maternal metabolic dysfunctions (yes; no) [ 33 ], alcohol use (yes; no) [ 34 ], tobacco use (yes; no) [ 35 ], maternal iron supplementation (yes; no) [ 36 ], maternal folic acid supplementation (yes; no) [ 37 ] during pregnancy, and sex of children (male; female) [ 38 ] (Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%